Microwave-Assisted Synthesis of Benzaldehyde Derivatives and their Biological Activity - Kadam, Prasad Dilip; Nagargoje, Ganpat Ram; Bondge, Abhay Shivajirao; Momin, Kalimoddin Inayatsab; Panchgalle, Sharad Pandit; More, Vijaykumar Shivdas (International Journal of Pharmaceutical Investigation, 2025)
Background The study focuses on the synthesis of novel 4-Hydrazinyl-7H-Pyrrolo[2,3-d] Pyrimidine (HPP) derivatives using microwave-assisted synthesis starting from substituted benzaldehydes (a-j) and HPP in the presence of a strong acid. Materials and Methods The synthesized compounds were validated through mass spectrometry, 1H NMR and infrared spectroscopy. The antibacterial activity was tested using the disc diffusion method against two gram-positive bacteria (Staphylococcus aureus MCC 2010 and Bacillus subtilis MCC 2010) and two gram-negative bacteria (Pseudomonas aeruginosa MCC 2080 and Escherichia coli MCC 2412). Dimethylformamide (DMF) was used as a control, with standard antibiotics serving as the positive control. Results The antimicrobial screening revealed that all synthesized compounds exhibited significant antibacterial activity. Notably, several compounds displayed greater activity compared to the reference drugs used in the study. Conclusion The microwave-assisted synthesis of HPP derivatives from substituted benzaldehydes yielded compounds with promising antibacterial properties, surpassing the effectiveness of some standard antibiotics.
Keywords: Pyrrolopyrimidinehydrazide; Substituted benzaldehydes; Anti-microbial screening; Antifungal activities